Changes in the metabolic processes, cytomorphology, and histology of the fish Carassius gibelio exposed to 2,4,6-trinitrotoluene - Khromykh, N. O.; Sharamok, T. S.; Yesipova, N. B.; Marenkov, O. M.; Korzhenevska, P. O.; Gasso, V. Y.; Petrov, I. A. (Regulatory Mechanisms in Biosystems, 2025)
The environmental impact of explosive weapons in Ukraine occurs during hostilities and will take place in the post-war p e riod due to decomposition of unexploded ordnance and release of toxic compounds. Of this, 2,4,6-trinitrotoluene (TNT) is the primary ingredient, however, its effect on the freshwater hydrobionts has not been sufficiently studied. We aimed to establish in the model experiment the biochemical and histological changes in the tissue of Carassius gibelio , which may serve as biomarkers of exposure and the effect of TNT, and to predict the functional status of fish in polluted post-war waters. High induction of GST activity and LPO processes was revealed in the liver, gills, and muscles of the fish both under acute (8 hours at concentration 35 mg/L) and chronic (21 days at concentration 5 mg/L) TNT action, and assessed as the biomarkers of toxic exposure. The modulation of redox balance and detoxification intensity in the fish body can be considered as a biochemical adaptation of C. gibelio to long-term TNT action at low concentration. The changes in liver cells and nuclei morphometric indices, and the histopathological changes in the hepatocytes and gill structure were assessed as the biomarkers of TNT ’s toxic effects on C. gibelio . The lipoid dystrophy of hepatocytes and hypertrophy of the gill epithelium reflected the toxicant-induced metabolic modulation and can be considered as a morpho-physiological adaptation of the fish to the chronic TNT action at low concentr a tion. However, such abnormalities as increase in nucleus area/cell area ratio, binucleation, and karyolysis in hepatocytes, as well as the lamellae distortion and dilation of the lamellar apical tips in the gills indicated irreversible changes that reduce the vitality of the fish and dec rease the possibility of C. gibelio ’s complete adaptation even to low-dose TNT exposure. The obtained results highlight the need to study the natural water ecosystems of Ukraine contaminated with explosives to assess the current condition and survival prospects of the hydrobionts.